Phenotypic and genotypic features of the full-term newborns with delayed conjugation jaundices in relation to gender of the child - O. K. Botvin'yev; A. I. Kolotilina; I. N. Razumovskaya; A. V. Yeremeyeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To detect phenotypic and genotypic features of the full-term newborns with delayed conjugation jaundice in relation to gender of the patient.Material and methods. The group of full-term children (n=251) with delayed conjugation jaundice was investigated, that have been divided in two subgroups according to gender. All patients underwent complex clinical and laboratory, instrumental and immunologic investigation. Features of pregnancy and delivery course, weight and height scores and children disease spectrum, blood groups and Rhesus factor were investigated.Results. It was known, that prevailing genotypic changes in boys – increased proportion of 0 (I) groups and decreased proportion of A (II) blood group, as well as increase of proportion of phenotypes 0 Rh + and decrease of A Rh + in boys prevail in comparison to girls and control group, while in girls environmental factors (complicated course of pregnancy and delivery) have more pronounced effect. Boys and girls differ by disease spectrum. Assessment of these diseases shows, that state of girls was more severe.Conclusions. The original study allows to conclude, that children with delayed conjugation jaundice in neonatal period belong to risk group for development of complications at action of harmful external factors over the liver.